Centesimus Annus: A critical Jewish perspective - Green, Ronald M. (Journal of business ethics, 1993)
The author reviews a series of deep affinities between the Catholic social teaching embodied in Pope John Paul II's recent encyclical,Centesimus Annus, and traditional Jewish teachings about economic justice. At the same time, the author maintains that from a Jewish perspective there is a “disquieting” feature to this recent papal letter. It presents twentieth century history in ways that mute or conceal the role some earlier papal teaching played in the rise of corporatist states, with their authoritarian regimes and xenophobic nationalism.Centesimus annus thus obscures the complex contribution Catholic social teaching made to the events leading up to the Holocaust of European Jewry.